Improving VBAC rates: the combined impact of two management strategies. (30th July 2014) - Gardner, Kate; Henry, Amanda; Thou, Steven; Davis, Greg; Miller, Trent
<x xml:space="preserve">Abstract</x> Background Caesarean section rates in Australia have risen to >30%, with repeat caesarean delivery the most common indication. One method of reducing caesarean delivery rates is to increase rates of vaginal birth after caesarean section (VBAC). Aims To determine the combined effect of two management strategies on the rates of successful VBAC in women experiencing their first pregnancy following primary caesarean section. Methods Prospective cohort study from May 2009 to October 2010 at a metropolitan Australian teaching hospital. The strategies studied were (i) allocating responsibility for VBAC candidates attempting labour to the hospital's three high‐risk obstetric consultants and (ii) implementing a next birth after caesarean (NBAC) antenatal clinic designed to counsel and support women deciding on mode of birth for their next pregnancy after a primary caesarean section. Data were collected from Obstetrix, a NBAC logbook and medical records of 396 eligible women who gave birth during the study period. Results Overall VBAC rates improved from 17.2% in 2006 prior to implementation of the combined strategies, to 27.0% over the studied period (P < 0.001). Of those women who desired and attempted a VBAC, the success rate was 64.4%. Regression analysis identified an increased likelihood of attempted vaginal birth where malpresentation was the indication for previous caesarean, while Eastern Asian ethnicity was associated with increased likelihood of choosing repeat caesarean. Conclusions A dedicated NBAC clinic and more consistent approach to labour management can help improve VBAC rates. Further targeted counselling towards women with previous malpresentation and/or East Asian descent may further improve VBAC attempt rates.